Novel hub genes associated with pulmonary artery remodeling in pulmonary hypertension - Tan, Rubin; You, Qiang; Yu, Dongdong; Xiao, Chushu; Adu-Amankwaah, Joseph; Cui, Jie; Zhang, Ting (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary hypertension (PH) is a life-threatening disease with complex pathogenesis. According to etiology, PH is divided into five major groups in clinical classification. However, pulmonary artery (PA) remodeling is their common feature, in addition to bone morphogenetic protein receptor type 2; it is elusive whether there are other novel common genes and similar underlying mechanisms. To identify novel common hub genes involved in PA remodeling at different PH groups, we analyzed mRNA-Seq data located in the general gene expression profile GSE130391 utilizing bioinformatics technology. This database contains PA samples from different PH groups of hospitalized patients with chronic thromboembolic pulmonary hypertension (CTEPH), idiopathic pulmonary artery hypertension (IPAH), and PA samples from organ donors without known pulmonary vascular diseases as control. We screened 22 hub genes that affect PA remodeling, most of which have not been reported in PH. We verified the top 10 common hub genes in hypoxia with Sugen-induced PAH rat models by qRT-PCR. The three upregulated candidate genes are WASF1, ARHGEF1 and RB1 and the seven downregulated candidate genes are IL1R1, RHOB, DAPK1, TNFAIP6, PKN1, PLOD2, and MYOF. WASF1, ARHGEF1, and RB1 were upregulated significantly in hypoxia with Sugen-induced PAH, while IL1R1, DAPK1, and TNFA1P6 were upregulated significantly in hypoxia with Sugen-induced PAH. The DEGs detected by mRNA-Seq in hospitalized patients with PH are different from those in animal models. This study will provide some novel target genes to further study PH mechanisms and treatment.